1995
DOI: 10.1128/mcb.15.11.6283
|View full text |Cite
|
Sign up to set email alerts
|

Subregions of the Adenovirus E1A Transactivation Domain Target Multiple Components of the TFIID Complex

Abstract: Transcriptional activation by the adenovirus E1A 289R protein requires direct contacts with the TATA box-binding protein (TBP) and also displays a critical requirement for TBP-associated factors (TAFs) (T.G. Boyer and A. J. Berk, Genes Dev. 7:1810-1823, 1993; J. V. Geisberg, W. S. Lee, A. J. Berk, and R. P. Ricciardi, Proc. Natl. Acad. Sci. USA 91:2488-2492, 1994; W. S. Lee, C. C. Kao, G. O. Bryant, X. Liu, and A. J. Berk, Cell 67:365-376, 1991; and Q. Zhou, P. M. Lieberman, T. G. Boyer, and A. J. Berk, Genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 46 publications
0
62
0
Order By: Relevance
“…There appear to be at least two domains in TAF II 250 important for binding the large pocket of Rb (Figure 8). One domain is found within the amino terminus of TAF II 250, whereas the second lies near to or overlaps with the RAP74 (Ruppert and Tijan, 1995) and E1A binding domains (Geisberg et al, 1995). The mapping analysis demonstrates that the large pocket of Rb can bind to both of these domains in TAF II 250, but that the amino terminus of Rb is unable to bind to the amino terminus of TAF II 250.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…There appear to be at least two domains in TAF II 250 important for binding the large pocket of Rb (Figure 8). One domain is found within the amino terminus of TAF II 250, whereas the second lies near to or overlaps with the RAP74 (Ruppert and Tijan, 1995) and E1A binding domains (Geisberg et al, 1995). The mapping analysis demonstrates that the large pocket of Rb can bind to both of these domains in TAF II 250, but that the amino terminus of Rb is unable to bind to the amino terminus of TAF II 250.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to binding TBP and other TAFs, TAF II 250 has also been shown to bind the RAP74 subunit of TFIIF (Ruppert and Tijan, 1995), as well as adenovirus E1A (Geisberg et al, 1995) and HSV-ICP4 (Carrozza and DeLuca, 1996). We have previously demonstrated that Rb can associate with TAF II 250, regulating Sp1-mediated transcription .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Rb family of transcriptional corepressors bind to CR1 and CR2, the CBP/p300 family of acetyltransferases bind to the N-terminal region and CR1, whereas CtBP1 and CtBP2 associate with the C-terminal CR4 domain (Whyte et al, 1989;Dyson et al, 1992;Boyd et al, 1993;Eckner et al, 1994;Arany et al, 1995). CR3, exclusive to the E1A13S protein, binds to proteins involved in transcriptional activation, such as TATA binding protein (TBP), Mediator 23 (Med23) and associated transcription factors (ATFs), various transcription factors and proteasome components (Lee et al, 1991;Green, 1990, 1994;Geisberg et al, 1994Geisberg et al, , 1995Boyer et al, 1999;Wang and Berk, 2002;Rasti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Deacetylation of histone N-terminal tails can reverse this process and hypoacetylated regions of chromatin are transcriptionally less accessible. E1A interacts with various chromatin modifying proteins, (reviewed by Mymryk and Smith, 1997), some of which display histone acetyltransferase (HAT) activity, such as the transcriptional coactivators CBP/p300 (Ogryzko et al, 1996) and TAF II -250 (Geisberg et al, 1995;Mizzen et al, 1996). Other E1A binding proteins are directly associated with histone deacetylase proteins (HDAc's), like the Rb family of transcriptional repressors (Luo et al, 1998;Brehm et al, 1998;Magnaghi et al, 1998;Ferreira et al, 1998) and the transcriptional regulators YY-1 (Lee et al, 1995;Lewis et al, 1995;Yang et al, 1997) and CtBP (Schaeper et al, 1995;Sundqvist et al, 1998).…”
Section: Introductionmentioning
confidence: 99%